Temporal and spatial distributions of nutrients and trace elements (Ba, Cs, Cr, Fe, Mn, Mo, U, V and Re) in Mississippi coastal waters: Influence of hypoxia, submarine groundwater discharge, and episodic events. (1st March 2019) - Ho, Peng; Shim, Moo Joon; Howden, Stephan D.; Shiller, Alan M.
Abstract: A multi-year (2007–2011) chemical time series of eight stations in the western Mississippi Sound and northwestern Mississippi Bight was undertaken to examine the factors affecting chemical distributions in this dynamic region. Parameters measured include nutrients and selected dissolved trace elements (Ba, Cr, Cs, Fe, Mn, Mo, Re, U, and V). Key findings include the frequent development of bottom water hypoxia in this part of the Bight during late spring and summer, the likely contribution of submarine groundwater discharge (SGD) to the material flows (i.e., Ba, V and nutrients), and the effects of episodic events (i.e., tropical storms, cold fronts, the opening of the Bonnet Carré Spillway) on trace element distributions. In hypoxic bottom waters, enriched nutrients, Mn, and Ba as well as depleted V and Cr were commonly observed. Although dissolved Mn was often enriched to micromolar levels in hypoxic bottom waters, Fe (both dissolved and colloidal) was rarely over 100 nM, likely due to its rapid oxidation and removal. Similar to previous observations in Louisiana Shelf waters, the signal of bottom depletion of V and Cr during hypoxia is at times mixed upwards into surface waters. Consideration of the mass balances of dissolved Ba and V, in particular, supports the conclusion that SGD can be a significant contributor to the chemical mass balance in this region, not just for certain trace elements, but for nutrients, too. Interestingly, a seasonal change in the direction of the V flux from the sediments suggests that the chemical conditions (i.e., pH, EH, and/or DOC) of the groundwater are changing. During the study period, the Bonnet Carré Spillway was opened in April 2008 and May 2011. The spillway discharges Mississippi River to Lake Pontchartrain and ultimately to our study area, which is supported by the observation of an extended freshwater signal and low Cs across the Mississippi Sound and Bight during these two spillway openings. It is plausible that Mississippi Bight hypoxia was more severe due to increased nutrients and intense stratification induced by Mississippi River input following the opening of Bonnet Carré Spillway. Other episodic events included tropical storms, which can push Mississippi River water northward and make this material source potentially more important at those times. Important remaining questions from this study include the extent to which SGD and/or Mississippi River water are necessary for establishment and maintenance of hypoxia in the Mississippi Bight and the reasons for the seasonal change in the direction of the sedimentary V flux. Highlights: Multi-year time series of nutrients and metals east of Mississippi River Delta. Bottom water hypoxia observed during late spring and summer. Submarine groundwater discharge is a source for various chemical constituents. Seasonal change observed in direction of apparent sedimentary V flux. Episodic events affected hypoxia: tropical storms and Bonnet Carré Spillway opening.